1991
DOI: 10.1172/jci115088
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies elicited by pneumococcal antigens bear an anti-DNA--associated idiotype.

Abstract: There is evidence in both murine and human lupus that the production ofanti-DNA antibodies may be triggered by environmental antigens. To explore this further, we studied the serum of 10 nonautoimmune individuals immunized with a polyvalent pneumococcal polysaccharide vaccine. All 10 patients showed a rise in the titer of antipneumococcal antibodies bearing an anti-DNA-associated idiotype. The antipneumococcal response was specific as no idiotypic antitetanus antibodies were detected. Furthermore, no anti-DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 17 publications
1
30
0
Order By: Relevance
“…In support of this model, studies have demonstrated the presence of anti-doublestranded DNA (anti-dsDNA) antibodies in individuals after the onset of microbial infections (55). Furthermore, antiidiotype studies have shown structural similarities between antibacterial and anti-dsDNA antibodies (56)(57)(58). Molecular mimicry has also been studied in rheumatic fever, where there is well-documented crossreactivity between streptococcal M protein and cardiac myosin, and mAb that bind both Streptococcus and myosin and can induce histopathologic alterations in myocytes (59).…”
Section: Discussionmentioning
confidence: 93%
“…In support of this model, studies have demonstrated the presence of anti-doublestranded DNA (anti-dsDNA) antibodies in individuals after the onset of microbial infections (55). Furthermore, antiidiotype studies have shown structural similarities between antibacterial and anti-dsDNA antibodies (56)(57)(58). Molecular mimicry has also been studied in rheumatic fever, where there is well-documented crossreactivity between streptococcal M protein and cardiac myosin, and mAb that bind both Streptococcus and myosin and can induce histopathologic alterations in myocytes (59).…”
Section: Discussionmentioning
confidence: 93%
“…In humans, autoreactive antibodies are elicited by infection or by LPS-stimulation of normal B cells (67) and in response to infection and thus may be a feature of many normal immune responses. For example, the immune response against both Streptococcus pneumoniae and Klebsiella species is marked by the expression of anti-DNA associated idiotypes (68,69). Hib is a ubiquitous pathogen, and most individuals have acquired protective levels of antiHib PS Ab by 5 yr ofage (22).…”
Section: Discussionmentioning
confidence: 99%
“…However, the initial antigenic stimulus for the production of these autoantibodies remains unclear. Several lines of evidence suggest that microbial antigen may be a stimulus for their production: ( a ) in vitro mutation of an anti-pneumococcal antibody leads to loss of reactivity against pneumococcal antigen, and gain of specificity for dsDNA (13); ( b ) autoimmune NZB mice bred in germ-free conditions and not exposed to environmental microbes have greatly attenuated disease (14); ( c ) protective anti-bacterial antibodies and anti-dsDNA antibodies share idiotypic specificities (15); ( d ) patients with bacterial infection will have transiently elevated titers of anti-dsDNA antibodies that are idiotypically related to the anti-DNA antibodies of patients with SLE (16); and ( e ) cross-reactive antibodies binding both bacterial antigen and dsDNA can be isolated from both humans (17) and mice (18). Some of these cross-reactive antibodies binding both phosphorylcholine (PC), a dominant hapten on the pneumococcal cell wall, and dsDNA, can be protective against a bacterial challenge in vivo, but are also pathogenic and deposit in the kidney (18).…”
Section: Introductionmentioning
confidence: 99%